THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY WITH SATISFACTION AS AN INTERVENING VARIABLE ON SPIRITUAL TOURISM SALIB KASIH TARUTUNG - Swisiena Simorangkir; Ahmad Azmi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to find the effect of service quality on customer loyalty with satisfaction as an intervening at spiritual tourism Salib Kasih Tarutung. The population in this study were people who had just made a visit in the period January 2023 to January 2024, with a sample size taken as many as 75 visitors as respondents. The sampling technique used is random sampling. Primary data collection was carried out using a questionnaire wish was then analyzed quantitatively using the structural Equation Modeling- Partial Least Square Analysis method with the help of smart-PLS. As a result, service quality and customer satisfaction have a positive and significant effect on customer loyalty, then customer satisfaction has a positive and significant effect in mediating the relationship between service quality and customer loyalty.